Primary iris cyst and its surgical management: A case report - Kumar Biswas, Sujit; Rani Roy, Soma; Nazmun Nahar, Sayada; Hossain Tasha, Anzuman (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2024)
Aim: The aim of this study was to show a case of primary iris cyst and its surgical management. Case report: A 5-year-old child reported to our clinic with distorted and blurred vision in the left eye. The anterior segment examination of the left eye showed an oval, brownish-colored cyst, located in the inferior mid-iris touching the corneal endothelium. Ultrasound biomicroscopy (UBM) revealed that the cyst expanded anteriorly and just touched the corneal endothelium, causing localized corneal edema. The B-scan USG of the posterior segment was normal. The iris cyst was surgically removed, and after a month, the excised area healed with a small area of iris atrophy, and the corneal edema resolved. The resolved cyst area showed localized iris atrophy, the cornea became clear, and vision improved with a regular, round pupil. No recurrence was reported in the 6 months following the surgery. Conclusion: Primary iris cysts can be managed surgically in the early stages without any devastating ocular complications.